Abscopal effect leading to complete disappearance of extensive meningiomatosis after gamma knife radiosurgery: Case report - Aldakhil, Salman; Mathieu, David (Frontiers in Surgery, 2022)
Background and Importance: The abscopal effect is partial or complete tumor response in a separate site that was not the target of prior local treatment. There has been only 50 well-documented cases from 1960 to 2014. Our case is the first one of presumed low-grade meningioma demonstrating a possible response via the abscopal effect after single-fraction stereotactic radiosurgery. Clinical Presentation: A case of a 70-years-old female with extensive intracranial meningiomatosis who had complete disappearance of all tumors after gamma knife radiosurgery targeting the right petroclival part of the tumor. She had complete resolution of her symptoms, which included hearing loss, headache, ataxia and dysphagia. Conclusion: The abscopal effect is an extremely rare phenomenon after local radiation therapy of a remote tumor. Our case demonstrates that this can occur in remote meningiomas after single fraction GKRS of a different tumor.